The Role of Gratitude in Coping with Uncertainty: A Qualitative Analysis - Rahim, Aiman (Journal of Development and Social Sciences, 2024)
This study investigates the role of gratitude in managing uncertainty and its impact on psychological well-being. It explores how individuals use gratitude as a coping strategy during uncertain times and whether it alleviates anxiety, stress, and depression. Uncertainty is a major contributor to psychological disorders, and unpredictable events have been reported to increase stress. While gratitude has been shown to promote positive emotions and mental health, its ability to buffer the effects of uncertainty remains less explored. Using semi-structured interviews with 20 participants from Lahore, Pakistan, aged 18 to 65 years, this qualitative study examines how gratitude is practiced during uncertain periods. Thematic analysis revealed that gratitude enhances emotional resilience, fosters positive reframing, strengthens social bonds, and reduces anxiety and stress. Participants linked gratitude to a sense of control, purpose, and growth, with many expressing a greater appreciation for small joys. The study suggests integrating gratitude into mental health interventions, particularly for those facing uncertainty.